2008
DOI: 10.1520/gtj101307
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Specimen Preparation Method on the Stress-Strain Behavior of Sand in Plane-Strain Compression Tests

Abstract: Wanatowski, Dariusz and Chu, Jian (2008) Effect of specimen preparation method on the stress-strain behavior of sand in plane-strain compression tests. Geotechnical Testing Journal, 31 (4 A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Several studies have shown that the value of K 0 is related to factors such as soil type [6], relative density [7][8][9], stress history [10], soil structure [11], and anisotropy [12]. For sandy soil, the relative density D r is one of the most significant influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the value of K 0 is related to factors such as soil type [6], relative density [7][8][9], stress history [10], soil structure [11], and anisotropy [12]. For sandy soil, the relative density D r is one of the most significant influencing factors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yang et al [4] indicate that the dry funnel method leads to stronger samples under monotonic loadings than the wet tamping method, but Sze and Yang [5] indicates the opposite. In addition, most studies on sample reconstitution methods are carried out by using triaxial apparatuses [2,[5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reconstitution approaches have been developed in the past to mimic the in-situ fabric of granular materials deposited in different ways (e.g., alluvial deposits, fluvial deposits, compacted fills). It is well known that reconstitution techniques have a substantial effect on the soil fabric, which in turn affects shear strength properties (Oda, 1972a,b;Sze and Yang, 2014;Vaid et al, 1999;Wanatowski and Chu, 2008). If laboratory findings are to be transferred confidently to in-situ conditions, the reconstitution technique employed in the laboratory should resemble the natural deposition process.…”
Section: Sample Preparationmentioning
confidence: 99%